Deconstructing Diets: The Role of Wealth, Farming System, and Landscape Context in Shaping Rural Diets in Ethiopia - Rasmussen, Laura Vang; Wood, Sylvia L. R.; Rhemtulla, Jeanine M. (Frontiers in Sustainable Food Systems, 2020)
Dietary diversification is central to improving dietary quality and nutrition for food security. Several factors have been linked to higher diversity diets, including household wealth, market access, on-farm crop diversity and regional forest cover. How these factors combine in landscapes to shape diets, however, is not well understood. We take the Ethiopian context as a case study of how wealth, farming system type, and landscape context interact to explain household dietary profiles. Using cluster analysis on nationally representative data on household food consumption, we identify three distinct dietary profiles across rural Ethiopia: 1) A low diversity diet, 2) A diverse diet particularly rich in fruit and vegetables, and 3) A diverse diet also rich in oils, fats and sugars. We found that the low diversity diet was strongly associated with households in the bottom and middle wealth classes that were mostly involved in cereal-based farming, although not exclusively. In contrast, the diverse diet high in fruit and vegetables was primarily composed of households with coffee-agroforestry farming systems, and did not appear to be limited to any particular wealth class, although it was positively associated with forest cover. Households with a diverse diet profile also rich in oils, fats and sugars were stratified across multiple different farming types, situated closer to roads, and primarily came from the middle and top wealth classes. Finally, while forest cover was strongly associated with a dietary profile rich in fruits and vegetable and the pursuit of coffee-agroforestry farming, the forest cover in cereal-based systems was still significantly positively associated with the consumption of dark green leafy vegetables and fruits. This suggests that even small amounts of forest cover can contribute to healthy diets. These results, which illuminate how wealth, farming system type, and landscape context shape dietary profiles, have important implications for the design of effective food security policies in Ethiopia.